Yeshua : a guide to the real Jesus and the original church - Moseley, Ron (Lederer Books, Messianic Jewish Publishers, 2006)
[P]revious histories have generally left out the Jewish factor. By beginning their research with the later second- and third-century Church, after it became predominantly a Gentile organization, they have lost the history of the first hundred years and the necessary understanding of Jewish roots. Many difficult Hebraic phrases and theological dilemmas can be understood by investigating the original Jewish roots of the early Church. Today, scholars agree, on the most basic level, that Jesus was a Jew who was born, lived, and died, within first-century Judaism. His teaching methods, parables, proverbs, and symbolic style was characteristic of the Judaism of that day. Since both the Old and New Testaments are highly Hebraic, with the background, writers, culture, religion, traditions, and concepts being Hebrew, any analysis should be done from this perspective.